INTERACTIONS OF COPPER, ORGANIC ACIDS, AND SULFATE IN GOETHITE SUSPENSIONS - Ali M.A.; Dzombak D.A. (My University, 1996)
Sorption of copper and sulfate onto goethite (α-FeOOH) in aqueous solution is examined in Cu-SO4 binary-sorbate systems and in Cu-SO4-organic acid (either phthalic acid or chelidamic acid) ternary-sorbate systems. Compared to single-sorbate systems, sorption of Cu onto goethite was enhanced at low pH values in the presence of sulfate. Sorption data for Cu and SO4 in Cu-SO4 binary-sorbate systems were described with the Generalized Two Layer Model by proposing formation of a Cu-SO4 ternary surface complex. Addition of sulfate to a Cu-phthalic acid binary sorbate system had little effect on Cu sorption. However, addition of sulfate to Cu-chelidamic acid binary-sorbate systems resulted in significant reduction of Cu sorption at low pH values, primarily due to competition for surface sites between sulfate and Cu-chelidamic acid ternary surface complexes. While organic acids such as humic substances can potentially influence sorption of metal ions, results from this study suggest that the extent of such influence may be strongly dependent on the presence of other sorbing anions, such as sulfate. Sorption of Cu and SO4 in Cu-SO4-organic acid ternary-sorbate systems was predicted reasonably well, based on surface reactions and equilibrium constants derived from fitting of sorption data from single- and binary-sorbate systems. These modeling results provide a validation of the extrapolation of sorption from simple systems to multicomponent systems through surface complexation modeling.